The India–Pakistan security crisis. Issue 3 (16th March 2019) - Unknown
Abstract : A 14 February Jaysh e-Mohammad terrorist attack killing Indian military personnel in the Indian state of Jammu and Kashmir triggered the worst escalation of India–Pakistan tensions in nearly two decades. De-escalation ensued, but, especially given that high-level diplomacy may not resume in the short term, better crisis-management tools are required to ensure that war is avoided.